Analisa Pengaruh Strategi Komunikasi CSR Melalui Media Sosial terhadap Reputasi Perusahaan (Studi Kasus pada Perusahaan Consumer Goods di Indonesia) - Muhammad Darwinsyah (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2018)
This study aims to analyze of effect of CSR communication strategy through social media to corporate reputation, especially consumer goods companies operating in Indonesia. The research method used is a combination of quantitative and qualitative methods. Quantitative method is done by analyzing the results of random distribution of questionnaires to 130 respondents. To strengthen the analysis, conducted in-depth interviews with relevant resource persons in several Consumer Goods companies in Indonesia. While qualitative methods to do the interview as well a review of the company's website and social media.The results of this study are almost all Consumer Goods companies in Indonesia using its website and social media to communicate their CSR program. The stronger the brand company and brand products from the company, the greater the amount of information being communicated.The results of this study indicate that CSR communication strategy through the company website and social media proved to affect the company's reputation. Suggestions for future research is to take samples of any other company in Indonesia, in addition to its Consumer Goods. Keywords: Corporate Social Responsibility, CSR Communications, CSR website, social media CSR, corporate reputation.